Continuous Positive Airway Pressure therapy improves the Quality of Life among Obstructive Sleep Apnea individuals in Pakistani Population - Madiha Moin, Faisal Asad, Saif-Ur-Rehman, Ubedullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Continuous Positive Airway Pressure therapy is the most recommended treatment for OSA patients. Aim: To investigate a possible correlation between the Quality of life in obstructive sleep apnea patient’s pre and post-adhering to continuous positive airway pressure therapy for six months and compare them with the non-exposed group. Methods: This cohort study enrolled a sample of 180 participants, of which 90 were exposed to CPAP and 90 were not exposed by non-random purposive sampling from the Sleep Lab where obstructive Sleep apnea was diagnosed through Polysomnography. In the clinic, demographic data including gender, age, height, weight, body mass index, ESS, and Calgary Sleep Apnea Quality of Life Index were recorded in pre-CPAP therapy questionnaires and repeated after 6 months. Results: After six months of effective continuous positive airway pressure therapy, there was a remarkable increase in all individuals' all-around quality of life as measured by the total Sleep Apnea Quality of Life Index score. Total SAQLI score before treatment was 3.04±0.2 and after treatment was 5.3±0.5 p < 0.01; Daily Functioning, 3.3±0.4 and 5.3±0.6; Social Interaction, 2.9±0.4 and 5.5±0.5; Emotional Functional, 2.9±0.5 and 5.1±0.5; Symptoms, 2.9±0.5 and 5.2±0.6 (p<0.001). In contrast, the SAQLI scores in non-exposed individuals became worsened after six months. For domains A, B, C, and D, the mean difference was 1.96±0.74, 2.50±0.64, 2.21±0.70, and 2.34±0.80 respectively, has a statistically significant correlation (p=0.00). Conclusion: In conclusion, the current investigation yields some significant findings. Six months of continuous CPAP usage can help patients feel less sleepy, increase their SAQLI scores, and significantly lessen OSA-associated symptoms. Keywords: Quality of Life (QOL), Calgary Sleep Apnea Quality of Life Index (SAQLI), Obstructive Sleep Apnea (OSA), Continuous Positive Airway Pressures (CPAP), Daytime Sleepiness, Karachi.